The oral history of modern architecture interviews with the greatest architects of the twentieth century - Peter, John 1917-1998 (Harry N. Abrams, Inc., 1994)
This unprecedented book and accompanying compact disc tell the story of modern architecture in the words of the people who created it. Based on interviews conducted over the course of 40 years with more than 60 of the world's most prominent architects and engineers, the volume is both an invaluable oral history and a broadly appealing look at the development of the modern style, animated by the architects' own observations, opinions, anecdotes, and humor. The architects' words and the author's brief comments are accompanied by 200 black-and-white photographs of the landmarks of modern architecture, including plans, sketches, and models. Each has a brief explanatory caption that augments information in the text. Large, original candid portraits of the architects - taken at the time of the interview - add to the personal and conversational nature of the book.